Classic psychedelic use is associated with reduced psychological distress and suicidality in the United States adult population. (March 2015) - Hendricks, Peter S; Thorne, Christopher B; Clark, C Brendan; Coombs, David W; Johnson, Matthew W
Mental health problems are endemic across the globe, and suicide, a strong corollary of poor mental health, is a leading cause of death. Classic psychedelic use may occasion lasting improvements in mental health, but the effects of classic psychedelic use on suicidality are unknown. We evaluated the relationships of classic psychedelic use with psychological distress and suicidality among over 190, 000 USA adult respondents pooled from the last five available years of the National Survey on Drug Use and Health (2008–2012) while controlling for a range of covariates. Lifetime classic psychedelic use was associated with a significantly reduced odds of past month psychological distress (weighted odds ratio (OR)=0.81 (0.72–0.91)), past year suicidal thinking (weighted OR=0.86 (0.78–0.94)), past year suicidal planning (weighted OR=0.71 (0.54–0.94)), and past year suicide attempt (weighted OR=0.64 (0.46–0.89)), whereas lifetime illicit use of other drugs was largely associated with an increased likelihood of these outcomes. These findings indicate that classic psychedelics may hold promise in the prevention of suicide, supporting the view that classic psychedelics' most highly restricted legal status should be reconsidered to facilitate scientific study, and suggesting that more extensive clinical research with classic psychedelics is warranted.